BEARING CAPACITY AND SETTLEMENT ANALYSIS OF BOREPILE USING MAYERHOF AND VESIC METHODS FOR LRT JAKARTA PROJECT PHASE 1B - Pius Favian Krispriyanto; Dyah Ayu Rahmawati Cupasindy (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2025)
This study presents a comprehensive analysis of the bearing capacity and settlement behavior of bored pile foundations for the Jakarta LRT Phase 1B project, specifically at Pier P64B. Given the challenging soil conditions characterized by soft to stiff clay, silty clay, and sandy silt layers with variable Standard Penetration Test (SPT) values, a deep foundation system using bored piles was adopted to ensure structural stability and minimize excessive settlements. The investigation employs both Mayerhof’s and Vesic’s empirical methods to evaluate pile bearing capacity, integrating site-specific soil parameters and load combinations modeled in SAP2000 in accordance with Indonesian National Standards (SNI) and American Concrete Institute (ACI) regulations. The analysis includes assessments of single pile and group pile capacities, elastic and consolidation settlements, and pile cap design. Results reveal that while Vesic’s method predicts slightly higher pile capacity than Mayerhof’s, both methods confirm the adequacy of bored piles with a 0.6 m diameter and 23 m depth for safely supporting the applied loads, with settlements maintained below the allowable limit of 0.16 m. Group pile efficiency and load distribution were also optimized, suggesting 20 piles as the most cost-effective and structurally sound configuration. Construction methodology and reinforcement detailing were developed accordingly. The total estimated foundation cost is approximately IDR 580 million, reflecting improved efficiency over prior designs. This study contributes practical insights for foundation design under similar geotechnical contexts and serves as a reference for ensuring foundation safety and cost-effectiveness in heavy infrastructure projects.